Cation-π Interactions and their Functional Roles in Membrane Proteins. Issue 17 (20th August 2021) - Infield, Daniel T.; Rasouli, Ali; Galles, Grace D.; Chipot, Christophe; Tajkhorshid, Emad; Ahern, Christopher A.
Graphical abstract: Highlights: Physicochemical characteristics are summarized. Cation- π abundance is in membrane proteins assessed via automated structural analysis. Methods to assess cation- π interactions are discussed. Examples of cation- π interactions in diverse protein types are highlighted. Abstract: Cation-π interactions arise as a result of strong attractive forces between positively charged entities and the π-electron cloud of aromatic groups. The physicochemical characteristics of cation-π interactions are particularly well-suited to the dual hydrophobic/hydrophilic environment of membrane proteins. As high-resolution structural data of membrane proteins bring molecular features into increasingly sharper view, cation-π interactions are gaining traction as essential contributors to membrane protein chemistry, function, and pharmacology. Here we review the physicochemical properties of cation-π interactions and present several prominent examples which demonstrate significant roles for this specialized biological chemistry.